2007
DOI: 10.1097/nen.0b013e31802c39a4
|View full text |Cite
|
Sign up to set email alerts
|

The ΔK280 Mutation in MAP tau Favors Exon 10 Skipping In Vivo

Abstract: Tau mutations in frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17) are associated with changes in alternative splicing of exon 10. The DeltaK280 mutation in exon 10 is exceptional because in vitro observations suggest a dramatic effect on microtubule binding, enhanced self-aggregation, as well as a decrease of the 4R/3R ratio by the ablation of an exon splicing enhancer element. Using immunohistochemistry, Western blotting, and electron microscopy on brain material with the DeltaK280 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 37 publications
1
45
1
Order By: Relevance
“…There was extensive pathology with gross and microscopic evidence of Alzheimer disease, dementia with Lewy bodies and vascular dementia. In contrast to the previously described case with a ΔK280 mutation (van Swieten et al, 2007), which had severe atrophy of the frontal and temporal cortex extending into the inferior parietal lobe, the present case showed no evidence of frontotemporal degeneration.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…There was extensive pathology with gross and microscopic evidence of Alzheimer disease, dementia with Lewy bodies and vascular dementia. In contrast to the previously described case with a ΔK280 mutation (van Swieten et al, 2007), which had severe atrophy of the frontal and temporal cortex extending into the inferior parietal lobe, the present case showed no evidence of frontotemporal degeneration.…”
Section: Resultscontrasting
confidence: 99%
“…No Pick bodies or ballooned Pick cells were seen in the hippocampus or in any other location. On the other hand, the other ΔK280 case described by van Swieten and co-workers (van Swieten et al, 2007) demonstrated relatively widespread Pick bodies and also, taupositive glial cells.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…We included the following: (i) deletion of lysine 280 (ΔK280) (Rizzu et al ., 1999; Momeni et al ., 2009), which leads to excess of 3R transcripts (van Swieten et al ., 2007) and enhances tau aggregation into PHFs (Rizzu et al ., 1999; Barghorn et al ., 2000); (ii) mutations in cysteines 291 and 322 (C291 and C322), whose oxidation increases propensity of tau aggregation (Barghorn & Mandelkow, 2002; Mo et al ., 2009); and (iii) mutations that mimic or disrupt phosphorylation in residues previously related to tau toxicity or aggregation propensity (Biernat & Mandelkow, 1999). We have found that these modifications have a different impact on the degradation of tau by each of the autophagic pathways, and on the way in which they affect functioning of these autophagic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…About half of the known mutations in tau influence the splicing of tau pre-mRNA, mostly resulting in a higher ratio of 4R-to 3R-tau, but occasionally resulting in a lower ratio (Goedert and Spillantini 2006;van Swieten et al 2007). A complete understanding of how this ratio influences the onset of a tauopathy is currently lacking.…”
Section: A-synuclein Vs B-synucleinmentioning
confidence: 99%